Endothelial adenosine kinase deficiency ameliorates diet-induced insulin resistance. Issue 2 (August 2019) - Xu, Jiean; Yang, Qiuhua; Zhang, Xiaoyu; Liu, Zhiping; Cao, Yapeng; Wang, Lina; Zhou, Yaqi; Zeng, Xianqiu; Ma, Qian; Xu, Yiming; Wang, Yong; Huang, Lei; et al.
Abstract : Insulin resistance-related disorders are associated with endothelial dysfunction. Accumulating evidence has suggested a role for adenosine signaling in the regulation of endothelial function. Here, we identified a crucial role of endothelial adenosine kinase (ADK) in the regulation of insulin resistance. Feeding mice with a high-fat diet (HFD) markedly enhanced the expression of endothelial Adk. Ablation of endothelial Adk in HFD-fed mice improved glucose tolerance and insulin sensitivity and decreased hepatic steatosis, adipose inflammation and adiposity, which were associated with improved arteriole vasodilation, decreased inflammation and increased adipose angiogenesis. Mechanistically, ADK inhibition or knockdown in human umbilical vein endothelial cells (HUVECs) elevated intracellular adenosine level and increased endothelial nitric oxide synthase (NOS3) activity, resulting in an increase in nitric oxide (NO) production. Antagonism of adenosine receptor A2b abolished ADK -knockdown-enhanced NOS3 expression in HUVECs. Additionally, increased phosphorylation of NOS3 in ADK -knockdown HUVECs was regulated by an adenosine receptor-independent mechanism. These data suggest that Adk -deficiency-elevated intracellular adenosine in endothelial cells ameliorates diet-induced insulin resistance and metabolic disorders, and this is associated with an enhancement of NO production caused by increased NOS3 expression and activation. Therefore, ADK is a potential target for the prevention and treatment of metabolic disorders associated with insulin resistance.